Introducing Lisrel a guide for the uninitiated - Diamantopoulos, A. (Adamantios); Siguaw, Judy A. (London : SAGE, 2000)
Introducing Lisrel provides a comprehensive introduction to Lisrel for structural equation modeling using a non-technical user-friendly approach. It shows the major steps associated with the formulation and testing of a model.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Lisrel (Computer file); Social sciences -- Statistical methods -- Data processing